Q: 3x3 - 24x2 plus 45x

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x3 - 24x2 + 45x = 3x(x2 - 8x + 15) = 3x(x2 - 3x - 5x + 15) = 3x[ x(x - 3) - 5(x - 3) ] = 3x(x - 5)(x - 3)

It is an algebraic expression that can be simplified to: 45x -16

(9x)2 +9x/(45x)2 +81= 9+9x/86

45x

(5x+4)(9x+9) FOIL First (5x*9x=45x**2) Outside (5x*9=45x) Inside (4*9x=36x) Last (4*9=36) 45x**2+45x+36x+36 45x**2+81x+36 9(5x**2+9x+4x)

Related questions

3x3 - 24x2 + 45x = 3x*(x2 - 8x + 15) = 3x*(x - 3)*(x - 5)

3x3 - 24x2 + 45x = 3x(x2 - 8x + 15) = 3x(x2 - 3x - 5x + 15) = 3x[ x(x - 3) - 5(x - 3) ] = 3x(x - 5)(x - 3)

It is an algebraic expression that can be simplified to: 45x -16

(9x)2 +9x/(45x)2 +81= 9+9x/86

45x

(5x+4)(9x+9) FOIL First (5x*9x=45x**2) Outside (5x*9=45x) Inside (4*9x=36x) Last (4*9=36) 45x**2+45x+36x+36 45x**2+81x+36 9(5x**2+9x+4x)

3x3=99+2=1111+3=14=14

what kind of polynomial is shown 3x3+x+1

3x3+12x = 3x(x2+4)

4x(4x^2 - 6x + 7)

88x+33=45x*56 88x+33=2520x 33=2432x x=0.013569

x(x + 9)(x + 5)